Screening of People with High Blood Pressure in Moscow Region - O. M. Drapkina; R. N. Shepel; E. S. Ivanova; E. S. Bulgakova; A. N. Kaburova; L. M. Zhamalov; Yu. D. Shalyagin; A. V. Kutcher; S. A. Vernadskiy (Рациональная фармакотерапия в кардиологии, 2019)
Aim. To perform an arterial hypertension (HT) screening for assessing the awareness of Moscow Region citizens about high blood pressure (BP) and draw their attention to this important risk factor.Material and methods. The screening was performed as a part of Standardized International Screening Study "May Measurement Month 2018” in five towns of Moscow Region: Domodedovo, Balashikha, Mytishchi, Solnechnogorsk, Klin. 510 participants (324 females, 186 males) were involved, aged from 18 to 86 years (median age 42 [28;57] years). People over 1 8 years were asked to measure BP levels and fill out a questionnaire: age, gender, height and weight, previous BP measurement date, bad habit (tobacco smoking, alcohol consumption), cardiovascular diseases and type 2 diabetes history, previous high BP levels and antihypertensive drugs taking. Elevated BP was considered systolic BP (SBP) ≥140 mm Hg and/or diastolic BP (DBP) ≥90 mm Hg. Mechanical and automatic tonometers were used.Results. Increased BP was registered in 24% of participants. High BP levels were more common among men of working age and women older than working age. Increased BP was registered for the first time in 7% of the participants, and half of the participants who had previously taken antihypertensive therapy had increased BP levels. The highest prevalence of elevated BP levels was detected in obese men (55%).Conclusion. Regular preventive medical examinations have the task of health keeping and timely disease prevention. The continuity in the medical care may reduce the incidence of socially significant diseases.